Chromosome-level genome assembly of Niphotrichum japonicum provides new insights into heat stress responses in mosses - Zhou, Xuping; Peng, Tao; Zeng, Yuying; Cai, Yuqing; Zuo, Qin; Zhang, Li; Dong, Shanshan; Liu, Yang (Frontiers in Plant Science, 2023)
With a diversity of around 22,000 species, bryophytes (hornworts, liverworts, and mosses) represent a major and diverse lineage of land plants. Bryophytes can thrive in many extreme environments as they can endure the stresses of drought, heat, and cold. The moss Niphotrichum japonicum (Grimmiaceae, Grimmiales) can subsist for extended periods under heat and drought conditions, providing a good candidate for studying the genetic basis underlying such high resilience. Here, we de novo assembled the genome of N. japonicum using Nanopore long reads combined with Hi-C scaffolding technology to anchor the 191.61 Mb assembly into 14 pseudochromosomes. The genome structure of N. japonicum's autosomes is mostly conserved and highly syntenic, in contrast to the sparse and disordered genes present in its sex chromosome. Comparative genomic analysis revealed the presence of 10,019 genes exclusively in N. japonicum. These genes may contribute to the species-specific resilience, as demonstrated by the gene ontology (GO) enrichment. Transcriptome analysis showed that 37.44% (including 3,107 unique genes) of the total annotated genes (26,898) exhibited differential expression as a result of heat-induced stress, and the mechanisms that respond to heat stress are generally conserved across plants. These include the up-regulation of HSPs, LEAs and reactive oxygen species (ROS) scavenging genes, and the down-regulation of PPR genes. N. japonicum also appears to have distinctive thermal mechanisms, including species-specific expansion and up-regulation of the Self-incomp_S1 gene family, functional divergence of duplicated genes, structural clusters of up-regulated genes, and expression piggybacking of hub genes. Overall, our study highlights both shared and species-specific heat tolerance strategies in N. japonicum, providing valuable insights into the heat tolerance mechanism and the evolution of resilient plants.